Unintentional Intra-arterial Injection of 177Lu-PSMA-1 in a Patient With a Peritoneal Carcinosis Secondary to a Metastatic Prostate Cancer. (18th February 2023) - Kryza, David; Moreau, Aurélie; Badel, Jean Noël; Mognetti, Thomas; Giraudet, Anne Laure
Abstract: We report the case of an 81-year-old man presenting with peritoneal carcinosis secondary to a metastatic castrate-resistant prostate cancer addressed for 177 Lu-PSMA-1 therapy. During the second cycle, a diffuse uptake in his left forearm was observed on the 1-hour postinjection scintigraphy, typical for an accidental intra-arterial injection. Less than 24 hours postinjection, a full removal of the intra-arterial injection was observed in the man, without any pain or symptoms. Moreover, the man demonstrated an 85% PSA reduction and a CT OR following the RECIST 1.1 criteria after 3 cycles.